Cancer Treatment by Caryophyllaceae-Type Cyclopeptides - Houshdar Tehrani, Mohammad Hassan; Gholibeikian, Mohammadreza; Bamoniri, Abdolhamid; Mirjalili, Bi Bi Fatemeh (Frontiers in Endocrinology, 2021)
Cancer is one of the leading unleashed diseases which in the most cases ends with death and thus continues to be a major concern in human being worldwide. The conventional anticancer agents used in clinic often face resistance raised among many cancer diseases. Moreover, heavy financial cost refrain patients to continue treatment schedule. Bioactive peptides, active in several diverse areas against man’s health problems, such as infection, pain, hypertension and so on, have shown potential to be effective in cancer treatment and may give promise to be better candidates for combating cancer. Cyclopeptides, with naturally or synthetic origin, have several advantages over other drug molecules by their being low toxic, low immunogenic, easily amenable to several changes in their sequences, so giving many demanded homologues, have opened a new hope of discovering better compounds with desired properties in the field of challenging cancer diseases. Caryophyllaceae-type cyclopeptides have shown several biological activities including cancer cytotoxicity. These cyclopeptides have been discovered in several plant families, but mainly are from the Caryophyllaceae family. In this review, the summary of biological activities found for these cyclopeptides are given, the focus will be on the anticancer findings of these peptides. Among these cyclopeptides, information about Dianthins (including Longicalycinin A), isolated from different species of Caryophyllaceae, as well as their synthetic analogues will be detailed. Finally, by comparing their structures and cytotoxic activities, finding the common figures of these kinds of cyclopeptides as well as their possible future place in clinic for cancer treatment will be put forward.